Changes in the News Paradigm in Online Journalism - Nabilah Rahadatul ‘Aisy (AMK : Abdi Masyarakat UIKA, 2025)
This research studies how individuals trust news spread via social media, because up to now there are still many news readers who are consumed by hoaxes or fake news. It also studies the salient differences in the presentation of news in online media. This research uses a quantitative approach with a survey method, the questionnaire instrument was designed via the Google Form platform while secondary data was obtained from literature and previous research. The data collection technique in this research was Regional Random Sample with a sample of 30 respondents, the majority of whom came from students at the Sunan Ampel State Islamic University, Surabaya and East Java. The process of distributing questionnaires has been carried out since September 2025. The test results concluded that 50% of news paradigms influence online journalism, so that the way of thinking and acting in news writing must be aligned with online journalism or the ethical code and rules in journalism.